Tracing the peak of Neoglacial cooling on the Western Antarctic Peninsula: The Little Ice Age moraines of Marguerite Bay - Ciner, Attila; Yildirim, Cengiz; Sarikaya, M. Akif; Klanten, Yohanna; Oliva, Marc; Seong, Yeong Bae; Yu, Byung Yong (Pergamon Press Ltd., 2025)
Constraining the timing of glacial advances and retreats is crucial for understanding paleoclimate and forecasting future trends. While the retreat of the western side of the Antarctic Peninsula ice sheet since the Last Glacial Maximum (ca. 26-19 ka) is relatively well-documented, the Neoglacial period (ca. 4 to 0.2 ka), primarily represented by moraine and lacustrine records, remains poorly constrained. In this study, we compiled a non-exhaustive list of potentially datable, fresh-looking moraines located near active glaciers along Marguerite Bay, the largest bay in the Western Antarctic Peninsula. Subsequently, we utilised 10Be Terrestrial Cosmogenic Nuclide (TCN) surface exposure dating on three moraine complexes adjacent to three distinct glaciers: the Shoesmith and Erinç moraines on Horseshoe Island and the Erol Moraine on the Calmette Peninsula. The results from boulders, cobbles, and pebbles (n = 9) of the Shoesmith lateral moraine yielded a mean exposure age of 496 ± 79 years, coinciding with the Little Ice Age (LIA) in the Northern Hemisphere and marking the end of the Neoglacial period. The boulders (n = 4) collected from the right lateral moraine of the Erinç Glacier, which consists of several recessional ridges, are challenging to interpret owing to significant age scatter. Multiple scenarios indicate a late Neoglacial advance with an error-weighted mean landform age of 1163 ± 403 years. We also tentatively attribute the formation of the undated innermost moraine ridge, located just a few tens of metres from the current glacier front, to the LIA. The moraine boulders (n = 3) collected from the youngest end moraine of the Erol Glacier exhibit significant inheritance, with unusually high ages ranging from ca. 2 to 10 ka. This is likely due to limited subglacial erosion of boulders and/or short supraglacial transport, which do not permit the zeroing of previously accumulated nuclides. Nevertheless, the cross-cutting relationships between the Erol Moraine that overlie previously OSL- and 10Be-TCN-dated raised beaches indicate its formation during the LIA advance. We also highlight the complexities associated with asynchronous moraine formation and inheritance in glacial boulders that experience low rates of erosion. Overall, our data refine the chronology of the late Neoglacial period on the Western Antarctic Peninsula, highlighting the significance of the LIA in a region where its timing and duration had previously remained unclear.